Literature Review : Risk Factors of Anemia in Pregnancy Women - Ummi Azmi; Yenny Puspitasari (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2022)
In Indonesia, according to the results of Riskesdas (2018), the proportion of anemia in 2018 has increased to 48.9 % when compared to 2013 which was 37.1%. Anemia in pregnancy is a condition where a hemoglobin level is below 110 g / L in the first and third trimesters or a hemoglobin level below 105 g / L in the second trimester. Anemia during pregnancy will impact pregnancy, childbirth, and post-partum. The purpose of literature review is to summarize the risk factors of anemia in pragnancy women. Literature review was taken from 15 journals using a crosssectional study, population is pregnant women in the region. There are eight international journals and seven journals from Indonesia with the span of the last five years. Literature source was from Pubmed, BMC, and Google Scholar. There were 19 variables were statistically significant through bivariate and multivariate tests on the occurrence of anemia in pregnancy. These variables were age, ethnicity, education, parity, compliance with Fe tablets, economic status, nutritional status, trimester in pregnancy, gestational age, frequency of ANC, residence, income, family members, food insecurity, mother's diet, current clinical disease, parasitic infection, mothers do not use family planning, and body mass index (BMI).